Women & Public Policy A Revolution in Progress - CONWAY, M. Margaret (CQ Press, 1999)
The 20th century has witnessed dramatic changes in women's lives -- changes which in turn have transformed society. Women and Public Policy examines the ways in which this cultural change in the United States has created a need for public policy and how public policy has led to cultural change.Women and Public Policy discusses traditional issues that affect women -- education, employment, and health care -- and explores other, sometimes overlooked, topics such as insurance, marriage and family law, the criminal justice system, and child care.Each chapter opens with a vignette offering a glimpse into the life of an individual woman. An index, suggestions for further reading, and chronologies of major events are included.